Wooden breast myopathy on broiler breast fillets affects quality and consumer preference - Almeida Assuncao, Andrey Savio de [UNESP]; Garcia, Rodrigo Garofallo; Komiyama, Claudia Marie; Sena Gandra, Erika Rosendo de; Souza, Jacqueline Rosa de; Santos, Wellington dos; Caldara, Fabiana Ribeiro; Martins, Renata Aparecida [UNESP] (Springer, 2020)
Introduction The emergence of myopathies such as wooden breast in the poultry industry generally associated with the fast development of the breast muscle of broilers has provided changes in the morphological structure of muscle tissues, as well as problems of meat qualitative attributes. The aim of this study was to evaluate physical, chemical, qualitative, and sensorial attributes of broiler fillets associated with severity levels of wooden breast (WB) myopathy in a poultry slaughterhouse. Materials and methods Three hundred fillets in a poultry slaughterhouse were classified into three severity levels: normal (100 samples), moderate (100 samples), and severe (100 samples). Results: After identification, classification, and description of changes, fillets with a severe WB level presented higher levels of red (a*), yellow (b*), and final pH. The lowest shear force and the highest myofibrillar fragmentation index were observed in fillets with a severe level when compared with normal fillets. The collagen content increased according to severity level. Tasters better evidenced the characteristic taste of chicken meat when tasting fillets with a severe WB level when compared with normal and moderate fillets. The succulence and preference of the Brazilian testers increased according to the severity level of the myopathy. Conclusion In general, fillets with moderate and severe WB myopathy were affected not only in appearance but also in qualitative, physical, chemical, and sensory characteristics.
Keywords: Abnormalities; Collagen; Meat quality; Sensory; Texture